Natural killer activity in a medium-term multi-organ bioassay for carcinogenesis - Tozzi Spinardi, Ana Lúcia [UNESP]; Kaneno, Ramon [UNESP]; Marchesan Rodrigues, Maria Aparecida [UNESP]; Fávero Salvadori, Daisy Maria [UNESP]; Rocha, Noeme Sousa [UNESP]; Barbisan, Luís Fernando [UNESP]; Ribeiro, Lúcia Regina [UNESP]; Viana De Camargo, João Lauro [UNESP] (Wiley, 1999)
Natural killer (NK) cell activity was evaluated after the initiation and promotion steps in a medium-term multi-organ bioassay for carcinogenesis. NK cell activity was assessed in vitro by Cr51 release assay at the 4th and 30th weeks of the experiment. Male Wistar rats were sequentially initiated with N-diethylnitrosamine (DEN i.p.), N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN drinking water), N-methyl-N-nitrosourea (MNU i.p.), dihydroxy-di-N-propylnitrosamine (DHPN drinking water) and N,N'-dimethylhydrazine (DMH s.c.) at subcarcinogenic doses for 4 weeks (DMBDD initiation). One group was evaluated at the 4th week and the other was maintained without any further treatment until the 30th week. Two initiated groups were exposed through the diet to 2-acetylaminofluorene (2-AAF) or phenobarbital (PB), from the 6th until the 30th week. Five additional groups were studied to evaluate the effects of each initiator on NK activity. All groups submitted to initiation only, initiation plus promotion, or promotion only, developed significantly more preneoplastic lesions than the untreated control group. The main target organs for a tumor development in the initiated animals were the liver and the colon, irrespective of treatment with 2-AAF or PB. NK cell activity was not affected by exposure to genotoxic carcinogens after initiation, at the 4th week. Treatments only with PB or 2-AAF did not change NK cell activity. However, decreased NK cell activity was registered in the group only initiated with DMBDD and in the group given DMBDD+2-AAF. This late depression of NK cell activity at the 30th week could be related to the production of suppressing molecules by the tumor cells.
Keywords: Chemical carcinogens; Immune response; Multi-organ carcinogenesis; NK cell activity